Film collections and preservation practices in selected libraries in the University of the Philippines - Llarena, Claudette M.; Arlante, Salvacion M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study, Film Collections and Preservation Practices in Selected Libraries in the University of the Philippines, looks into the various methods of preservation employed by the UPFC Archives, the CMC Library, and the Main Library's Media Services Section.
The study focused on the causes of deterioration of the film collections, the methods of preservation used, and the effectiveness of said preservation methods.
The research found out that most of the film collections under the care of said institutions are in good condition although there are problems concerning temperature control and maintenance of collection. The preservation measures used help to maintain the state of the films.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Motion picture film collections -- Preservation. -- Philippines; Motion picture film collections -- Philippines -- Quezon City; University of the Philippines (Diliman) Libraries